2023
DOI: 10.1097/fm9.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcomes of SARS-CoV-2 and Variants in Pregnancy

Abstract: Pregnancy is a physiological state that predisposes women to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, a disease that can cause adverse maternal and perinatal outcomes. The severity of coronavirus disease 2019 (COVID-19) disease is known to vary by viral strain; however, evidence for the effects of this virus in pregnant women has yet to be fully elucidated. In this review, we describe maternal and perinatal outcomes, vaccination, and vertical transmission, among pregnant women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 132 publications
(329 reference statements)
0
0
0
Order By: Relevance
“…We found a lower frequency of NICU admission among term infants in the Delta period although previous studies have reported either higher risk or no difference between the pre-Delta and Delta predominance periods. 21,22 This may be due to differential missingness in the pre-Delta period compared to the Delta predominance period (Table 2). Future analyses can assess the impacts of disease severity and immunization status.…”
Section: Resultsmentioning
confidence: 99%
“…We found a lower frequency of NICU admission among term infants in the Delta period although previous studies have reported either higher risk or no difference between the pre-Delta and Delta predominance periods. 21,22 This may be due to differential missingness in the pre-Delta period compared to the Delta predominance period (Table 2). Future analyses can assess the impacts of disease severity and immunization status.…”
Section: Resultsmentioning
confidence: 99%